2015
DOI: 10.1007/s13277-015-4154-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of cullin proteins in gastric cancer

Abstract: The cullin proteins are a family of scaffolding proteins that associate with RING proteins and ubiquitin E3 ligases and mediate substrate-receptor bindings. Thus, cullin proteins regulate the specificity of ubiquitin targeting in the regulation of proteins involved in various cellular processes, including proliferation, differentiation, and apoptosis. There are seven cullin proteins that have been identified in eukaryotes: CUL1, CUL2, CUL3, CUL4A, CUL4B, CUL5, and CUL7/p53-associated parkin-like cytoplasmic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 108 publications
1
6
1
Order By: Relevance
“…High antigen KI-67 and CUL5 expression levels in tissues are associated with cancers [44,[52][53][54][55][56]. We observed increased serum concentrations of these proteins in patients with CKD in this study.…”
Section: Discussionsupporting
confidence: 60%
“…High antigen KI-67 and CUL5 expression levels in tissues are associated with cancers [44,[52][53][54][55][56]. We observed increased serum concentrations of these proteins in patients with CKD in this study.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, CUL7 overexpression promoted proliferation in glioma cells in our study. Although many previous studies have reported that CUL7 promoted tumorigenesis by suppressing P53 [10,40,41], CUL7 also promoted the proliferation of U251, a glioma cell line with mutated p53 [42], in our study; this indicates that CUL7 could have other independent pathways to promote the development of glioma. In this way, to attain the potential molecular mechanisms by which CUL7 promotes glioma development, we detected the expression changes of some key mediators of cell proliferation and apoptosis, including p21, p27, cyclin D1, CDK4, cyclin E1 and CDK2.…”
Section: Discussioncontrasting
confidence: 79%
“…Cul2 has been predicted to be a tumor suppressor protein because of its association with the von Hippel-Lindau gene and ubiquitinated HIFa degradation (18,19). However, it has also been reported that Cul2 is required for normal vasculogenesis and involved in cell-cycle regulation (20) and that it promotes gastric cancer progression (35,36). In our study, we analyzed 75 HCC tissues, and the results showed that the Cul2 expression level was not significantly correlated with HCC metastasis.…”
Section: Discussionmentioning
confidence: 71%